Orbital fractures and concurrent ocular injury in a New Zealand tertiary centre - Theis, Nicholas J.; Narsinh, Pritesh; Newlands, Samuel; Erasmus, Jason; Stack, Rebecca (Frontiers in Ophthalmology, 2023)
Orbital fractures are a common presentation to acute care and carry an associated risk of ocular injury, however, previous research has not investigated injury rates by fracture category. These patients are frequently assessed by non-ophthalmic clinicians, however, limited data exists regarding referral patterns and how this impacts recorded injury rates (1-3).We performed a retrospective review of all orbital fractures presenting to a tertiary hospital in Christchurch, New Zealand between March 2019 and March 2021. Data including mechanism of injury, fracture type, demographic characteristics, and associated ocular injury were recorded.284 patients with orbital fractures were identified. 41% of patients had isolated wall fractures, while 59% had complex orbitofacial fractures. Fractures were more common in males, and occurred more frequently in young individuals. The most common mechanism of injury was interpersonal violence (32%), followed by falls (23%). 41% of patients were reviewed by ophthalmology (n = 118). Of those, 33% had an associated ocular injury. Severe ocular injury (defined as vision threatening, requiring globe surgery or acute lateral canthotomy and cantholysis) occurred in 4.9% of those with formal ophthalmic review. 0.7% of patients required intraocular surgery or lateral canthotomy due to their orbital fracture.Orbital fractures have a high rate of concurrent ocular injury in our study population, though rates of subsequent intraocular surgery are low. There was no significant difference in injury rates between isolated and complex fracture categories. Vision-threatening ocular injury occurred in 4.9% of fractures.